Level of Knowledge on Acne Vulgaris and Its Treatment Among Undergraduates Medical Students at Universitas Sumatera Utara - Mohamad Khalid Khalid, Lily Khalidatussofina; Dina Arwina Dalimunthe (Talenta Publisher, 2023)
ABSTRACT Backgorund:Â Acne vulgaris (AV) is a skin disorder commonly found on late teens, young adults and most patients are females. The classic pathophysiology circulates the relationship between inflammation, bacterial colonization, sebum excretion and follicular epidermal hyperproliferation. Other factors may include diet, stress level, self-hygiene, and hormones especially in female patients.Â A proper diagnosis and the right treatment approach will help treat patient significantly. Sufficient knowledge on acne vulgaris and its treatment is important for a person to self-medicate or a visit to the dermatologist can be another option. Commonly used self-medication for acne are clindamycin and benzoyl peroxide (BPO). Treatment can either be single or combined therapy to achieve better results. Acne treatments might take some time to show its effects and it may also relapse. Objectives: The study aims to see the level of knowledge on acne vulgaris by the respondents. Methods: This cross-sectional study was conducted to medical undergraduates at Universitas Sumatera Utara. Results: 85.2% from total respondents have had acne before. 142 (55.5%) students chose to seek treatment with a dermatologist which majority of them are females (34.4%). Female students contribute the most with 160 responses. Most respondents are from age category of 16 to 21 (75.4%). Conclusion: Students do have the knowledge on acne vulgaris and its treatment hence almost half of them chose to self-medicate. Students are also aware that other treatment options are available. Keywords: acne vulgaris, behavior, Cutibacterium acnes, knowledge, treatment Â ABSTRAK Latar Belakang: Akne vulgaris (AV) merupakan kelainan kulit yang sering ditemukan pada remaja akhir, dewasa muda dan kebanyakan penderitanya adalah wanita. Patofisiologi klasik mengedarkan hubungan antara peradangan, kolonisasi bakteri, ekskresi sebum dan hiperproliferasi epidermal folikel. Faktor lain mungkin termasuk diet, tingkat stres, kebersihan diri dan hormon terutama pada pasien wanita. Diagnosis yang tepat dan pendekatan pengobatan yang tepat akan membantu merawat pasien secara signifikan. Pengetahuan yang cukup tentang akne vulgaris dan pengobatannya penting bagi seseorang untuk mengobati sendiri atau kunjungan ke dokter kulit bisa menjadi pilihan lain. Pengobatan sendiri yang umum digunakan untuk jerawat adalah klindamisin dan benzoil peroksida (BPO). Perawatan dapat berupa terapi tunggal atau kombinasi untuk mencapai hasil yang lebih baik. Perawatan jerawat mungkin membutuhkan waktu untuk menunjukkan efeknya dan mungkin juga kambuh. Tujuan: Mengetahui gambaran pengetahuan dan pemilihan pengobatan akne pada mahasiswa Fakultas Kedokteran Universitas Sumatera Utara. Metode: Menggunakan metode desain penelitian potong lintang (cross sectional) dengan membagikan kuesioner kepada mahasiswa/i Fakultas Kedokteran Universitas Sumatera Utara. Hasil: 85,2% dari total responden pernah menderita akne sebelumnya. 142 (55,5%) mahasiswa memilih berobat ke dokter spesialis kulit dengan mayoritas berjenis kelamin perempuan (34,4%). Mahasiswa perempuan berkontribusi paling banyak dengan 160 respon. Responden terbanyak adalah dari kelompok usia 16 sampai dengan 21 tahun (75,4%). Kesimpulan: Mahasiswa memiliki pengetahuan tentang akne vulgaris dan pengobatannya sehingga hampir separuh dari mereka memilih untuk berobat sendiri. Siswa juga menyadari bahwa pilihan pengobatan lain tersedia. Kata Kunci: akne vulgaris, Cutibacterium acnes, over-the-counter, pengetahuan, perilaku